Economic War and Multipolar Economic World - Ashik, Syod Ahsanul Islam; Afroje, Sahariya; Hossain, Nazmul (Advances in Social Sciences Research Journal, 2022)
This is an everchanging and ever-competitive global arena. It’s called globalization of economic affairs. After the WWII a significant number of international financial institutes and economic mechanisms including World Bank, IMF, SWIFT System, WTO (GATT), International Stock Exchanges as well as global Reserve currency have been developed to create a borderless economic world, called American World Order. Due to global market economy and borderless economic world whole world has become a global village and the movement of goods, capital and people has been eased and widened. Economic activities have been faster, diversified, and widespread in one hand and on the other hand the outer influence on an economy has become very significant. Inter-exchange of products and services and inter-dependability among the nations are the global scenarios in the modern world. On the contrary, these financial institutions and economic mechanisms are being used as western leverage and being politicized and weaponized to counter the rival states, causing economic volatility in national and global levels during last several decades. The main purpose of the study is to analyze the impacts of outer influence and politicization & weaponization of economic mechanism and international financial institutions on a particular economy and on global economy in large and potential ways to overcome the challenges. The study is mainly based on secondary sources of data including scholarly journal, articles, books, research materials, news of media outlets and other relevant sources pertaining to the subject. The finding of the study will contribute to counter the unusual economic situation, deter the counterproductive economic measures of hostile outsiders and suggest a mechanism and framework for an Alternative Economic System to form a multipolar economic world to neutralize the western domination.